PENGARUH PEMBENTUKAN DISPERSI PADAT PERMUKAAN KARVEDILOL DENGAN BERBAGAI BAHAN PENDISPERSI TERHADAP KELARUTAN DAN LAJU DISOLUSI - Triesya Arthari, Felia
Carvedilol is anti-hypertension agent who works by reducing vascular resistance and thereafter causing vasodilation of arteries. Carvedilol classified to Biopharmaceutical Classification System (BCS) class II since it has both low solubility and dissolution rate while having high permeability membrane. One of the means of ehancing solubility and dissolution rate from poorly soluble drug in water can be done various methods, including surface solid dispersion. The purpose of this study is to enhance the solubility and dissolution rate of carvedilol with a surface-solid dispersion system. This study also include literature study encompasses various aspects to increase solubility and dissolution of carvedilol by surface solid dispersion methods. The following steps of the experiment have been carried out, including the formation of a calibration curve, the formation of surface solid dispersions of carvedilol, the physical mixture and recrystallization of carvedylol results as well as the determination of carvedilol content. Surface solid dispersion with microcrystalline cellulose as a carrier at a ratio of 1:1; 1: 5 and 1:10 obtained percent yield 92.4%, 97.14% and 100.467% respectively, while the crosccarmellose sodium as a carrier at a ratio of 1: 1; 1: 5 and 1:10 obtained percent yield 90.3%, 89.12% and 84.72% respectively. The results of the determination of content in surface solid dispersions with microcrystalline cellulose as a carrier at a ratio of 1: 1; 1: 5 and 1:10 were 78.01 %, 96.05 % and 108.69 % respectively, while the crosccarmellose sodium as a carrier at a ratio of 1: 1; 1: 5 and 1:10 were 81.24 %, 152.45% and 65.31 % respectively. Based on literature studies, a surface solid dispersion system with crosscarmellose sodium and microcrystalline cellulose can increase the rate of dissolution and solubility. Furthermore, the increase in dissolution rate with sodium crosscarmellose carrier was more significant when compared with microcrystalline cellulose carrier. K